2017
DOI: 10.13057/biodiv/d180201
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in abundance and diversity of copepods in Mond River estuary, Bushehr, Persian Gulf

Abstract: Abstract. Hedayati A, Pouladi M, Vazirizadeh A, Qadermarzi A, Mehdipour N. 2017. Seasonal variations in abundance and diversity of copepods in Mond River estuary, Bushehr, Persian Gulf. Biodiversitas 18: 447-452. The present study was carried out to investigate the abundance and biodiversity of copepods from Mond River (MR) estuary, Bushehr, the Persian Gulf during 4 seasons and their relationships with environmental factors. The water samples were collected in mid-season from spring 2012 to winter 2013 for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…As well as, the reduction of the density of phytoplankton. This found is agree with Hedayati et al [63].…”
Section: Shannon-weiner Diversity Index (H')supporting
confidence: 93%
“…As well as, the reduction of the density of phytoplankton. This found is agree with Hedayati et al [63].…”
Section: Shannon-weiner Diversity Index (H')supporting
confidence: 93%
“…Low value of this index in winter may be related to the decreasing of water temperature which is the main reason for reduction of egg production and number of immature stages; as well as, reduced the density of phytoplankton. These findings corresponded with Hedayati et al (2017) indicated that the values of species index for copepod decreased with the decreasing of water temperatures.…”
Section: Ecological Indices Species Richness Index (D)supporting
confidence: 85%
“…On the other hand, the values of this index raised in spring, this may be returned to the increasing of sunlight intensity and photosynthesis rates this in turn increases phytoplankton production which is subsequently increased Copepoda diversity (Hedayati et al, 2017).…”
Section: Ecological Indices Species Richness Index (D)mentioning
confidence: 99%